Processing of Chlamydia abortus Polymorphic Membrane Protein 18D during the Chlamydial Developmental Cycle - Wheelhouse, Nick M.; Sait, Michelle; Aitchison, Kevin; Livingstone, Morag; Wright, Frank; McLean, Kevin; Inglis, Neil F.; Smith, David G. E.; Longbottom, David (PLOS ONE, 2012)
Background Chlamydia possess a unique family of autotransporter proteins known as the Polymorphic membrane proteins (Pmps). While the total number of pmp genes varies between Chlamydia species, all encode a single pmpD gene. In both Chlamydia trachomatis (C. trachomatis) and C. pneumoniae, the PmpD protein is proteolytically cleaved on the cell surface. The current study was carried out to determine the cleavage patterns of the PmpD protein in the animal pathogen C. abortus (termed Pmp18D). Methodology/Principal Findings Using antibodies directed against different regions of Pmp18D, proteomic techniques revealed that the mature protein was cleaved on the cell surface, resulting in a100 kDa N-terminal product and a 60 kDa carboxy-terminal protein. The N-terminal protein was further processed into 84, 76 and 73 kDa products. Clustering analysis resolved PmpD proteins into three distinct clades with C. abortus Pmp18D, being most similar to those originating from C. psittaci, C. felis and C. caviae. Conclusions/Significance This study indicates that C. abortus Pmp18D is proteolytically processed at the cell surface similar to the proteins of C. trachomatis and C. pneumoniae. However, patterns of cleavage are species-specific, with low sequence conservation of PmpD across the genus. The absence of conserved domains indicates that the function of the PmpD molecule in chlamydia remains to be elucidated.